A integração do ensino médio à educação profissional técnica no Brasil e os rebatimentos no estado do Ceará: das intenções às realizações - Costa, César Lima (2012)
This dissertation is focused on the integration of High School (HS) with Professional Technical Education (PTE), in this work it is intended to overcome the classic historical division between the Professional Education, which is said to be addressed to the working class, versus the Propaedeutic Education that forms in Brazilian context the dominant politics class. In order to achieve our goals, It is adopted a dialectical method of investigation added to a critical exposition of the studied object based on a Marxist analysis on the legal documentation and bibliography related to the theme. All these comments were empowered by data coming from questionnaires and interviews which were extracted from the field research investigation which took place on the educational system of Ceará that has worked with the method HS to PTE since its beginning in 2008. In the development of the research, it was pointed out the general historical context of the educational problematic in Brazil, showing the tendency to structural duality as the hallmark in Brazilian education, we also highlighted the theme of the educational policies in the 1990s, taking emphasis on the mediation between education and the global changes since the 1960s, paradigm, greatly, characterized by the binomial productive restructuring and governmental counter-reformulation. In this overview, we went through an analysis of the president Lula’s government in which was originated the political integration HS/PTE. First, we debated the contributions of legal integration policy, with emphasis on political and ideological struggles that resulted in the Decree No. 5.154/2004 and the subsequent changes made to the LDB No. 9394/1996 concerning the discussed matter. Secondly, we debated the set of governmental actions related to HS, expressed by the Education Development Plan (EDP) and the consequences of integration policy HS/PTE in the state of Ceará, enforcing the political reconfigurations of the local bourgeoisie expressed in the adoption of the conception of the world as business derived mainly from the philosophy of socio-educational stuff as a business technology (abbreviated in Portuguese as TESIS), all those elements put together as theoretical reference and base management to the formation / implementation of HS model in Ceará. The results mentioned in this research showed that in Brazil it is notorious the division between the formation of working class educational versus the formation of dominant/politic class, this context was influenced differentially by the historical movements of the structural crisis of capital in the current stage of development of the productive forces. That context, added to an exacerbated absence of a national education system, influenced the federal agencies. In this sense, we can conclude that education in its various forms and levels has been influenced by the capitalist logic, then, it has been legitimizing the classist status quo, enforcing, in this way, the maintenance/ deepening of social asymmetries, adapting the human conscience to the capitalist system. In this scene, it is crucial to overcome this paradigm, so the public school rises as a "trench" to be defended against the capitalist purpose, a defense based on the purification of the educational system from the deliberated forces of capitalism. We also concluded the urgency of developing the cultural level of the masses subordinated to the limits of capital, fighting against the untouchable bases of extraction of surplus value what originates the social division of labor/ private ownership of the means of production.